Framing Architectural Identity of Aceh After Two Contemporary Events - Muhammad Naufal Fadhil; Aji Sofiana Putri (Universitas Sebelas Maret Surakarta, 2024)
Socio-political conditions in a region have a substantial impact on architectural identity. Two contemporary events in Aceh: the 2004 tsunami and the Free Aceh Movement and the Republic of Indonesia conflict, impacted socio-political circumstances and architectural identities. This study revisits the architecture after those two contemporary events in Aceh by examining the socio-political processes and dynamics underlying its architectural representations. The research incorporates literature, theoretical data, and Aceh's architectural and urban history. This research also ties socio-political data to architectural phenomena after the two contemporary events. This research frames two main periods of architectural history after two contemporary events, namely Post-Tsunami 2004 and Post-Conflict. In the post-tsunami 2004 period, there are three architectural phenomena: the shifting perspective of safe and vulnerable places, the new 'Tsunami' typology, and the revival of the old typology. While in the post-conflict period, there are also three architectural phenomena: the search for Islamic architecture, the return of regionalism, and architecture anomalies.